“É possível mudar?”: práticas pedagógicas de professores de sala de aula que atuam na alfabetização de estudantes com deficiência intelectual - Dantas, Lilianne Moreira (2019)
This study investigates the pedagogical practices of regular classroom teachers in the literacy of students with intellectual disabilities in a primary school of the public network of HorizonteCE. As a theoretical-methodological contribution, it was based on the presuppositions of collaborative action research that advocates the implication of the subjects in the research development, enabling formation from the lived reality for reflection and promotion of changes. For the collection of data were developed application of scripts, participant observation and individual and collective reflective sessions. The data were collected in a municipal public school involving three teachers from the initial years corresponding to the literacy cycle and the teacher of the Specialized Educational Assistance (AEE). Students with intellectual disabilities (ID) were interviewed subjects. As a theoretical reference, the historical-cultural approach of Vygotsky was used. We address as thematic areas of discussion: inclusive pedagogical practices, collaborative practice and literacy of students with intellectual disabilities. The results were organized and analyzed from the change movements based on Barbier. Asresults, the research initially showsthat: a movement of change has been established in the pedagogical practices of regular classroom teachers in order to meet the learning specificities of students with intellectual disabilities, as well as that there is still a practice pedagogy that limits the progress of these students, pointing to the need for continuing education that considers the challenges of the classroom that is intended to be inclusive. From the individual and collective reflective sessions verified changes in the following aspects: qualification of mediation with the student with ID; emergence of strategies that collaborate with teaching, such as curricular differentiation and Individualized Educational Planning; movements of changes in pedagogical practices that were once supported by a pedagogy of negation; understanding and establishing an organized and efficient collaborative practice between regular and AEE; and advances in the conceptual levels of reading and writing of students with ID. However, it has been observed some permanences regarding the constitution of pedagogical practices that do not favor the advance of concepts by the students and the question of the systematization of the collaborative practice.